The episodic resurgence of highly pathogenic avian influenza H5 virus - Xie, Ruopeng; Edwards, Kimberly M.; Wille, Michelle; Wei, Xiaoman; Wong, Sook-San; Zanin, Mark; El-Shesheny, Rabeh; Ducatez, Mariette; Poon, Leo L. M.; Kayali, Ghazi; Webby, Richard J.; Dhanasekaran, Vijaykrishna (Nature (London), 2023)
Highly pathogenic avian influenza (HPAI) H5N1 activity has intensified globally since 2021, increasingly causing mass mortality in wild birds and poultry and incidental infections in mammals 1 – 3 . However, the ecological and virological properties that underscore future mitigation strategies still remain unclear. Using epidemiological, spatial and genomic approaches, we demonstrate changes in the origins of resurgent HPAI H5 and reveal significant shifts in virus ecology and evolution. Outbreak data show key resurgent events in 2016–2017 and 2020–2021, contributing to the emergence and panzootic spread of H5N1 in 2021–2022. Genomic analysis reveals that the 2016–2017 epizootics originated in Asia, where HPAI H5 reservoirs are endemic. In 2020–2021, 2.3.4.4b H5N8 viruses emerged in African poultry, featuring mutations altering HA structure and receptor binding. In 2021–2022, a new H5N1 virus evolved through reassortment in wild birds in Europe, undergoing further reassortment with low-pathogenic avian influenza in wild and domestic birds during global dissemination. These results highlight a shift in the HPAI H5 epicentre beyond Asia and indicate that increasing persistence of HPAI H5 in wild birds is facilitating geographic and host range expansion, accelerating dispersion velocity and increasing reassortment potential. As earlier outbreaks of H5N1 and H5N8 were caused by more stable genomic constellations, these recent changes reflect adaptation across the domestic-bird–wild-bird interface. Elimination strategies in domestic birds therefore remain a high priority to limit future epizootics. Recent resurgences of highly pathogenic avian influenza H5 viruses have different origins and virus ecologies as their epicentres shift and viruses evolve, with changes indicating increased adaptation among domestic birds.